Engineering Lactococcus lactis as cell factory for the production of plant limonene - Shaili, Nurul `Aishah (2019)
Limonene and perillyl alcohol (POH) are plant monoterpenes which give a significant contribution to the aroma of most essential oils due to its pleasant fragrance. Both compounds are synthesized via two pathways known as the mevalonate or 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway by metabolizing geranyl pyrophosphate (GPP) substrate. These compounds have been studied to exhibit an anti-cancer effect against several types of cancer including colorectal cancer. However, isoprenoid metabolic engineering work has been mostly studied in Escherichia coli. To date there is no report on limonene and POH production in Lactococcus lactis . In this study, L. lactis was developed as a heterologous host for the production of limonene using the recombinant L. lactis as an oral delivery for anti-cancer compounds against colorectal cancer in the future. Limonene synthase (LS) and cytochrome P450 alkane hydroxylase (ahpGHI ) genes were cloned and expressed in L. lactis NZ9000 host. Western blot analysis using mouse IgG His-Tag monoclonal antibody revealed a successful LS expression by L. lactis with the size of ~56 kDa. The expression ahpGHI of gene by L. lactis was not detected by Western blot despite induction time up to 48 h. According to RT-PCR analysis, the ahpGHI gene was transcribed only after 24 h post induction, although protein expression of ahpGHI gene remained unresolved. GC-MS analysis result showed that limonene production was optimum after 24 h post induction. However, production of limonene was still low (~4.0 ppm) and did not reach the LD50 value required to inhibit the proliferation of cancer cells. Therefore metabolic engineering was attempted to increase the production of limonene by introducing the 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) and mvk genes in the bacterial host. There are two types of HMGR that was used which are mvaA gene from L. lactis and HMGI from baker's yeast. The constructs containing mvaA and mvk genes from L. lactis was described as pNZ : LSMM plasmid, wheras the one from baker's yeast written as pNZ:LS: HMGI plasmid. The recombinant L. lactis carrying pNZ:LSMM plasmid successfully enhanced the limonene production over three folds (4.9-15.1 ppm) after 24 h of induction. Trypan blue exclusion test was conducted to investigate the viability of SW480 colorectal cancer cell after treatment with recombinant L. lactis producing limonene. From the result it showed that the cell viability was decreased in dose-dependent manner with the highest inhibition effect observed at 29.2% after 4 h of treatment at MOI 1500:1. The outcomes of this study shed light on the potential of food grade L. lactis for plant proteins and bioactive compounds production which prospectively leads to a delivery system for anti-cancer compounds.